Fracture Assessment of the Weld–Base Metal Interface of High-Strength Steel Weld Joint - Zhong, Z.P.; Liu, H.; Ma, J.J. (Проблемы прочности, 2018)
The brittle fracture of the weld joint at low stresses is controlled by high-strength steel characteristics and welding defects. Based on fracture mechanics, the fracture behavior of the weldbase metal interface of a high-strength steel weld joint was studied to reveal the critical locations of the latter. From tensile fracture experiments of 45 steel welded specimens, the load–displacement curve and the fracture modes of weld joints were obtained. The results indicate that the critical loads and fracture modes are influenced by the crack slope angle. The maximum load of interface fracture in weld joints is less than that of the failure in the base metal mainly related to the existence of initial defects in the weld joint. The fracture surface morphology was also detected. It is considered that the fracture surface is influenced by different fracture locations and different microstructure of the weld and base metals. In addition, the critical stress intensity factors of a weld interface crack were calculated based on the critical load and the finite element linear extrapolation method. The linear fracture assessment criteria were proposed, which will be applicable to safety evaluation for the weld joints of high-strength steel structures. Хрупкое разрушение сварного соединения при низких напряжениях зависит от характеристик высокопрочной стали и дефектов сварки. Принципы механики разрушения послужили основой изучения поведения поверхности контакта металл сварного шва–основной металл при разрушении сварного соединения высокопрочной стали для выявления критических точек на последнем. По результатам испытаний на разрушение при растяжении сварных образцов из стали 45 построена кривая прогиб–нагрузка и получены виды изломов на сварных соединениях. Показано, что угол наклона трещины оказывает влияние на критические нагрузки и виды изломов. Максимальная нагрузка, вызывающая разрушение поверхности контакта сварного соединения, ниже нагрузки разрушения основного металла, которое зависит главным образом от дефектов, изначально присутствовавших в сварном соединении. Установлены морфология поверхности излома и влияние на нее месторасположения изломов и микроструктуры металла сварного шва и основного металла. Критические коэффициенты интенсивности напряжений для трещины на поверхности контакта рассчитывали на основании критической нагрузки с помощью конечноэлементного метода линейной экстраполяции. Предложены критерии оценки линейного разрушения, которые могут быть использованы для проверки надежности сварных соединений в конструкциях из высокопрочной стали.